2017
DOI: 10.3892/mmr.2017.6873
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-504 inhibits p53-dependent vascular smooth muscle cell apoptosis and may prevent aneurysm formation

Abstract: Abdominal aortic aneurysm (AAA) is a common disease that is associated with the proliferation and apoptosis of vascular smooth muscle cells (VSMCs). VSMCs are regulated by microRNAs (miRNA). The aim of the present study was to identify miRNA sequences that regulate aortic SMCs during AAA. miRNA-504 was identified using a miRNA PCR array and by reverse transcription-quantitative polymerase chain reaction analysis, and its expression levels were observed to be downregulated in the aortic cells derived from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Histological studies have revealed that AAA is associated with the impairment of apoptotic and inflammatory functions of vascular smooth muscle cells (VSMCs). VSMCs are the key source of elastin, which provides the elasticity of the aortic wall (3). VSMC apoptosis can reduce the levels of elastin, leading to the expansion of the aortic wall and ultimately resulting in alterations to the elasticity and remodeling of the abdominal aortic wall (4).…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies have revealed that AAA is associated with the impairment of apoptotic and inflammatory functions of vascular smooth muscle cells (VSMCs). VSMCs are the key source of elastin, which provides the elasticity of the aortic wall (3). VSMC apoptosis can reduce the levels of elastin, leading to the expansion of the aortic wall and ultimately resulting in alterations to the elasticity and remodeling of the abdominal aortic wall (4).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, searching for novel therapeutic methods is imperative to reduce mortality of this disease. AAA is a multifactorial disease characterized by extensive vascular inflammation and degenerative elasticity of aortic wall caused by vascular smooth muscle cells (VSMCs) apoptosis reduced elastin production [5,6]. Thus, inhibiting apoptosis of VSMCs and alleviating inflammation are mainstream directions for biomarkers and therapeutic approaches of AAA.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis-related pathways were also found in the functional enrichment analysis of target genes. (26,27). The second category of ASP is extrinsic ASP.…”
Section: Discussionmentioning
confidence: 99%